The Role of Motivation in Student Achievement: A Cognitive-Behavioral Perspective - Yeltriana, Yeltriana; Sariani, Novita (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
This study aims to explore the role of motivation in student achievement using a cognitive-behavioral perspective. Through a quantitative survey approach, data were collected in several high schools in Indonesia. The questionnaire used measured the level of student motivation, including intrinsic and extrinsic motivation, as well as academic achievement as measured by report card grades. Data analysis was conducted using a simple linear regression test to examine the relationship between motivation and academic achievement. The results showed that there was a positive and significant influence between student motivation and academic achievement. The average score of students with high motivation was significantly better than students with low motivation. This study supports the cognitive-behavioral theory which states that motivation plays an important role in the learning process and achievement of results. This study recommends the importance of developing programs that can increase student motivation in the context of education, as an effort to improve overall academic achievement.